Dukungan Suami dengan Kecemasan Ibu Hamil Menjelang Persalinan pada Masa Pandemi Covid-19 - Nursyam, Dian Eka; Sari, Novi Maya (Jurnal Sehat Mandiri, 2023)
Anxiety in pregnant women is anxiety that arises, especially in the third trimester of pregnancy until the time of delivery, during this period pregnant women feel anxious about various things such as whether the baby is born normally or not, the pain they feel (Usman, 2016). The aim of this research is to analyze the relationship between husband's support and pregnant women's anxiety before giving birth during the Covid-19 pandemic. The type of research is analytical with a cross sectional approach.The independent variable is husband's support and the dependent variable is anxiety before giving birth in the era of the Covid-19 pandemic.The population of this study was 99 pregnant women and a sample of 30 pregnant women, the sampling technique was total sampling. Research results Severe anxiety in pregnant women (20%) is because pregnant women experience anxiety because they experience sleep disturbances due to frequent urination, and 13.3% of them receive less support from their husbands, namely there are husbands who are very busy working so their wives don't pay attention to their mothers. Statistical test The statistical test used the Chi-Square test, obtained P Value: 0.030 <α: 0.05. It is hoped that the husband can provide support to his wife, providing motivation so that the husband is ready to accompany his wife to have her pregnancy checked by a midwife or at the health center until the birth occurs.